Analisis Pragmalingusitik Terhadap Peribahasa Nasihat Minangkabau - Mutia Irhamni (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research aims to analyze Minang advice proverbs pragmatically and syntactically. Minang advice proverbs pragmatically have a distinctive meaning, and syntactically can be analyzed by complexity type, voice and mood. The research method uses qualitative-quantitative. With the research theory of Searle (1969) and Bach Harnish (1979), the theory used is to analyze the speech act function of Minang Kabau advice proverbs based on locution, illocutionary perlocution, felicity function and directive derivative function and communicative function of meaning of Minang Kabau advice proverbs to syntactic function. The data is sourced from a book by Idrus Hakim entitled "Petatah -Petitih Bahasa Minang" and research by Iqbal Sahib Dishar and Marwa Ali Qassim entitled "Pragmalinguistics Study of the Speech act of Warning in Arabic Health Proverbs". The results show that the proverbs of advice are articulated as the interests of the listener rather than the speaker of the proverb. Advice is indirectly expressed through pragmatic analysis of communicative and directive function sentences through two types of sentences: multilevel compounding